Afiksasi Dalam Bahasa Sunda Dialek Baduy Kampung Ciboleger Banten - Fitriani, Dea; Juansah, Dase Erwin; Solihat, Ilmi (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
In this research, researchers took stories from the Baduy community of Ciboleger village. There are various types of speech that undergo the affixation process. This research uses a qualitative approach with descriptive methods, namely research in which the analysis is presented in the form of written descriptions accompanied by explanations and explanations. The data source in this research is the Baduy community. Data collection techniques in research use observation techniques, interview techniques, recording techniques, and skilled free-involved listening techniques. In this research, after the data analysis process was complete, the researcher carried out data validity. The way to check whether the data is valid or not is through a validator. The results of the research can be concluded that the speech of the Baduy people of Ciboleger Village was found to have undergone a lot of data that underwent an affixation process. The findings produced in the research regarding affixations in the speech of the Baduy community of Ciboleger Village totaled 26 data as follows: (1) prefix affixations totaling 11 data; (2) suffix affixation of 8 data; (3) Confix affixation of 7 data.